Emergence of Acinetobacter baumannii ST730 carrying the blaOXA-72 gene in Brazil - Pagano, Mariana (2016)
Over the last decade, Acinetobacter baumannii resistant to carbapenems has emerged in many medical centres and has been commonly associated with high morbimortality. In Brazil, this resistance is mainly attributed to the spread of OXA-23-producing clones and, to a lesser extent, to OXA-143-producing clones. Here, we describe, for the first time, two OXA-72-producing A. baumannii isolates in southern Brazil to a broad spectrum of antibiotics, except polymyxin B and tigecycline. Molecular typing by multilocus sequence typing (MLST) demonstrated that both OXA-72-producing isolates belong to a new sequence type (ST), ST730, which was recently identified in OXA-23-producing A. baumannii isolates in São Paulo, Brazil. We demonstrate that the two A. baumannii ST730 isolates carrying blaOXA-72 share a common ancestral origin with the blaOXA-23 producers in Brazil. This observation reinforces the importance of strain-typing methods in order to clarify the dynamics of the emergence of new clones in a geographic region.